Textile Technologies and Tissue Engineering: A Path Toward Organ Weaving. Issue 7 (29th February 2016) - Akbari, Mohsen; Tamayol, Ali; Bagherifard, Sara; Serex, Ludovic; Mostafalu, Pooria; Faramarzi, Negar; Mohammadi, Mohammad Hossein; Khademhosseini, Ali
Abstract : Textile technologies have recently attracted great attention as potential biofabrication tools for engineering tissue constructs. Using current textile technologies, fibrous structures can be designed and engineered to attain the required properties that are demanded by different tissue engineering applications. Several key parameters such as physiochemical characteristics of fibers, microarchitecture, and mechanical properties of the fabrics play important roles in the effective use of textile technologies in tissue engineering. This review summarizes the current advances in the manufacturing of biofunctional fibers. Different textile methods such as knitting, weaving, and braiding are discussed and their current applications in tissue engineering are highlighted. Abstract : Textile technologies have recently attracted great attention as potential biofabrication tools for engineering tissue constructs. Here, we discuss the current advances in the manufacturing of fibers and their assembly using textile techniques with a focus toward several key parameters, such as physiochemical characteristics of generated fibers and fabrics. Finally, the emerging directions of the biotextile technologies are highlighted.